Photoinduced Liquefaction of Azobenzene‐Containing Polymers. Issue 25 (30th January 2018) - Weis, Philipp; Tian, Wei; Wu, Si
Abstract: Light can liquefy some solid azobenzene‐containing polymers (azopolymers) by photoisomerization. Two types of photoinduced liquefaction of azopolymers have been reported: (1) polarized light can guide solid azopolymers "flow" along the polarization direction, which is called directional photofluidization and has been used for inscription of surface relief gratings (SRGs); (2) recently, some of us found that light can switch the glass transition temperatures ( T g ) of azopolymers and induce reversible solid‐to‐liquid transitions of these azopolymers. This Minireview demonstrates and compares directional photofluidization and photoinduced reversible solid‐to‐liquid transitions of azopolymers. Potential applications based on photoinduced liquefaction of azopolymers are highlighted and some remaining challenges in the field of photoinduced liquefaction of azopolymers are discussed. Abstract : Let it flow ! This Minireview demonstrates that solid azopolymers can be liquefied using light due to photoisomerization. Two distinct phenomena will be introduced: (1) directional photofluidization based on photoinduced trans‐cis‐trans cycling; and (2) solid‐to‐liquid transition based on glass transition temperature change of azopolymers due to trans ‐to‐ cis photoisomerization. We highlight potential applications and discuss remaining challenges in photoinduced liquefaction of azopolymers.